Application of Chemical Coagulants and Biopolymers for Sewage Sludge Dewatering - Arvand, M.; Shemshadi, R.; Zeynalov, N.A.; Efondiov, A.A. (Asian Journal of Chemistry, 2010)
In this work, effects of chemical coagulants [Fe2(SO4)3, Al2(SO4)3, FeCl3 and CaO] and biopolymers (chitin, carboxymethylcellulose (CMC) and chitosan) on sewage sludge dewatering were studied. According to the results, Fe2(SO4)3was the most suitable substance for dewatering of the returned activated sludge and FeCl3 was found to be the best coagulant for the aerobic digested sludge. The results showed that sludge dewatering speed compared with control samples increased by about 77.6 and 80.5 %, respectively. Also, among natural polymers being used, chitin having the lowest consumption level in comparison with other coagulants increased the dewatering speed for the digested sludge by about 59.5 %. In this case, the sludge moisture content compared with that of the control decreased by 12.8 %. In all cases, chitosan had a negative effect on the dewatering speed and reducing the sludge moisture content. The effect of carboxymethylcellulose on decreasing the sludge time to filteration was also negligible.